2009
DOI: 10.1186/1471-2164-10-194
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Enterococcus faecalis from healthy Norwegian infants

Abstract: Background: Enterococcus faecalis, traditionally considered a harmless commensal of the intestinal tract, is now ranked among the leading causes of nosocomial infections. In an attempt to gain insight into the genetic make-up of commensal E. faecalis, we have studied genomic variation in a collection of community-derived E. faecalis isolated from the feces of Norwegian infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 44 publications
(78 reference statements)
1
67
0
Order By: Relevance
“…We demonstrated that phage03 deletion resulted in a decline of E. faecalis JH2-2 infectivity both in C. elegans and in G. mellonella larvae. In agreement with previous reports that have described the absence of phage03 in the genome of E. faecalis food isolates (45) and its enrichment among clonal lineages associated with nosocomial diseases (17,40), we detected the presence of phage03 in the genome of CC2 strains E. faecalis V583, MMH594, and HH22. BLAST searches against the available E. faecalis genomes showed that this phage03-like element was also found with a higher incidence in nosocomial isolates whereas it is rarely found in other strains of different origins (see Table S8 in the supplemental material).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We demonstrated that phage03 deletion resulted in a decline of E. faecalis JH2-2 infectivity both in C. elegans and in G. mellonella larvae. In agreement with previous reports that have described the absence of phage03 in the genome of E. faecalis food isolates (45) and its enrichment among clonal lineages associated with nosocomial diseases (17,40), we detected the presence of phage03 in the genome of CC2 strains E. faecalis V583, MMH594, and HH22. BLAST searches against the available E. faecalis genomes showed that this phage03-like element was also found with a higher incidence in nosocomial isolates whereas it is rarely found in other strains of different origins (see Table S8 in the supplemental material).…”
Section: Discussionsupporting
confidence: 80%
“…The availability of large amounts of whole-genome sequencing data has facilitated in silico comparative analyses of the gene content of enterococcal strains representing a wide spectrum of biotypes, clonal lineages, and isolation sources. As result, these investigations have contributed to the determination of the size and composition of the E. faecalis core genome (40,50), the genetic background for antibiotic resistance (51), and the identification of potential virulence factors that can influence the bacterial lifestyle (16). However, there is still a lack of understanding of how the genetic variation between commensal and nosocomial strains could explain the alleged behavior associated with these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, six out of seven loci were identical to sequence type 16 from an isolate found in a Norwegian infant's fecal sample (39). Consistent with physiological characterization of the latter isolate, we found genes linked to antibiotic transport or modification and genes encoding virulence factors including collagen-binding adhesin, aggregation substance, enterococcal surface protein, gelatinase (gelE), and cytolysin (39). Additional predicted virulence factors included an exfoliative toxin A and a serine protease known to be transcribed with gelE (40).…”
Section: Analyses Of Two Ecologically Distinct Citrobacter Subpopulatmentioning
confidence: 86%
“…Here we report the complete genome sequence of the commensal E. faecalis 62, which was isolated from a healthy Norwegian infant (20). This isolate has the multilocus sequence type ST66, which is not part of any clonal complex related to nosocomial infections (20).…”
mentioning
confidence: 99%